PROJECT PLANNING PEMBANGUNAN JALAN TOL YOGYAKARTA – BAWEN PAKET 1 SEKSI 1 STA.67+500 – STA.76+300 - Hruhita, Kautsar Argya; Setiono, Joko; Utoyo, Suselo (Prokons: Jurnal Teknik Sipil, 2024)
The Yogyakarta–Bawen Toll Road Infrastructure Project Package 1 Section 1 is a government-initiated construction project aimed at enhancing development and connectivity in southern Java. During the construction phase, delays occurred due to suboptimal implementation of pre-determined strategies and methods, resulting in failure to meet the targets for cost, time, and quality. To achieve the cost, time, and quality targets in similar projects, this research focuses on alternative project planning, including project organizational structure, site layout and traffic management, construction methods and strategies, quality planning, Health, Safety, Environment, and Security (HSES) plans, scheduling, and budget execution plans. The development of this alternative project planning required data such as the detailed engineering design (DED), work plans and specifications, unit price analysis, the 2022 Goods and Services Price Standards of Sleman Regency, and support from Microsoft Excel and Microsoft Project for scheduling and budget calculation planning. The final outcomes of the alternative project planning include functional organizational structure, site layout and traffic management planning using calculations of traveling distance and safety index, construction strategies divided into elevated work zones with 4 work areas and at-grade work zones with 5 work areas, quality planning based on work plans, specifications, and technical requirements, HSES planning, including the establishment of an organizational structure, emergency response action plans, IBPRP (Incident-Based Problem Response Plan) tables, efforts to achieve a zero-accident target, HSES support equipment, and HSES scheduling, scheduling planned for a total of 579 working days, budget execution plan amounting to IDR 3,083,558,817,300.